2004
DOI: 10.1111/j.1600-0501.2004.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate occlusal loading of Osseotite implants in the lower edentulous jaw

Abstract: The results of this study suggest that the rehabilitation of the edentulous mandible by an immediate occlusally loaded hybrid prosthesis supported by five to six Osseotite implants represents a viable alternative treatment to classic delayed loading protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
2
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 19 publications
7
160
2
10
Order By: Relevance
“…Les résultats obtenus dans la présente étude font état d'un taux de succès implantaire de 98,3 % à trois ans, et confirment que l'emploi d'implants texturés Osséotite ® est compatible avec le protocole de mise en charge immédiate [30,31]. L'échec d'un implant avant la réalisation de la prothèse définitive apparue chez le patient prenant de la Métadone ® ne permet pas d'établir un lien entre la prise de ce médicament et la perte de l'implant.…”
Section: Discussionunclassified
“…Les résultats obtenus dans la présente étude font état d'un taux de succès implantaire de 98,3 % à trois ans, et confirment que l'emploi d'implants texturés Osséotite ® est compatible avec le protocole de mise en charge immédiate [30,31]. L'échec d'un implant avant la réalisation de la prothèse définitive apparue chez le patient prenant de la Métadone ® ne permet pas d'établir un lien entre la prise de ce médicament et la perte de l'implant.…”
Section: Discussionunclassified
“…When the DAE implants were immediately loaded in mandibles, a cumulative survival rate of 98.9 % was achieved for up to 48 months of follow-up, while the prosthetic cumulative survival rate for the same period was 100 %. Marginal bone loss at the immediately loaded implants was within the generally accepted conventional limits for standard delayed loading protocols [ 40 ]. Additional human biopsies revealed that under immediate loading the DAE may yield above 78 % of BIC after 4 months [ 41 ].…”
Section: Dual Acid Etchingmentioning
confidence: 99%
“…The surface was covered with collagen membrane and secured with interrupted sutures. The ball abutments were screwed to the implant body as adequate primary stability for immediate loading of implants was achieved [4,5].…”
Section: Techniquementioning
confidence: 99%